2020
DOI: 10.1177/0379572119876848
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance and Willingness to Pay for Instant Cereal Products With Food-to-Food Fortification in Eldoret, Kenya

Abstract: Background: Maize is the major food staple in East and Southern Africa, where food-processing industries are emerging fast. New low-cost extrusion cookers allow small enterprises to enter the market for processed cereals, including instant, fortified, and flavored products. Objective: Assess consumers’ interest and preferences for the new products. Methods: Consumers (n = 220) in Eldoret, Kenya, were invited to evaluate 4 new cereal products: (1) sifted maize flour mixed with sorghum, (2) instant sifted mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Concentration and drying, especially of edible substandard produce and by-products into shelf-stable plant fortificants, would expand fruit and vegetable processing enterprises and substantially contribute to a reduction in these losses. By-products such as pumpkin and okra leaves and pineapple and tomato peel are promising fortificants (Table 5), which would have smaller cost implications compared to the premium products (carrot and baobab powder) included in the calculations of De Groote et al (2020). In time, the expansion of plant food fortificant production should serve to bring down the cost of the fortificants and also generate a food ingredient value chain domestically.…”
Section: Costs Versus Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentration and drying, especially of edible substandard produce and by-products into shelf-stable plant fortificants, would expand fruit and vegetable processing enterprises and substantially contribute to a reduction in these losses. By-products such as pumpkin and okra leaves and pineapple and tomato peel are promising fortificants (Table 5), which would have smaller cost implications compared to the premium products (carrot and baobab powder) included in the calculations of De Groote et al (2020). In time, the expansion of plant food fortificant production should serve to bring down the cost of the fortificants and also generate a food ingredient value chain domestically.…”
Section: Costs Versus Benefitsmentioning
confidence: 99%
“…Recent research in Kenya has shown that FtFF of an instant cereal porridge flour with 20% dried carrot and baobab fruit would currently increase the net cost of the product by approximately 28% on account of the higher costs of these ingredients (De Groote et al., 2020). However, this and related research in Senegal revealed that consumers are willing to pay a significant premium for these products fortified with fruits and vegetables, an additional 12% in Kenya and 4 to 9% in Senegal (De Groote et al., 2018, 2020), which would significantly mitigate the additional cost.…”
Section: Consideration Of Best Practices In Implementation Of Plant‐bmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still uncertainty about how to effectively carry out nutrient supplementation and how to best reach the vulnerable populations. Therefore, this calls for a possibility of food to food fortification of widely consumed traditional staples like maize and sorghum to improve the nutritional content and hence reduce postharvest losses rather than devising schemes to distribute supplements (De Groote et al, 2020). In particular, plant based fortificants from the food system can be added to improve the nutritional content of traditional staple crops.…”
Section: Introductionmentioning
confidence: 99%
“…This paper attempts to account for product experience using HUT, where consumers tried the product for a few days at home using affective tests. The affective test seeks to assess the personal response (preference or acceptance) to a new product by a sample of representative consumers (De Groote et al, 2020). Two different products: ugali, a stiff porridge and uji, a thin porridge, products that are the most commonly prepared as staples by most consumers in Kenya were evaluated.…”
Section: Introductionmentioning
confidence: 99%